Solid‐State Isolation of Cyclic Alkyl(Amino) Carbene (cAAC)‐Supported Structurally Diverse Alkali Metal‐Phosphinidenides. Issue 1 (27th November 2020) - Kulkarni, Aditya; Arumugam, Selvakumar; Francis, Maria; Reddy, Pulikanti Guruprasad; Nag, Ekta; Gorantla, Sai Manoj N. V. T.; Mondal, Kartik Chandra; Roy, Sudipta
Abstract: Cyclic alkyl(amino) carbene (cAAC)‐supported, structurally diverse alkali metal‐phosphinidenides 2 –5 of general formula ((cAAC)P‐M) n (THF) x [2 : M=K, n =2, x= 4; 3 : M=K, n =6, x= 2; 4 : M=K, n =4, x= 4; 5 : M=Na, n =3, x= 1] have been synthesized by the reduction of cAAC‐stabilized chloro‐phosphinidene cAAC=P‐Cl (1 ) utilizing metallic K or KC8 and Na‐naphthalenide as reducing agents. Complexes 2 –5 have been structurally characterized in solid state by NMR studies and single crystal X‐ray diffraction. The proposed mechanism for the electron transfer process has been well‐supported by cyclic voltammetry (CV) studies and Density Functional Theory (DFT) calculations. The solid state oligomerization process has been observed to be largely dependent on the ionic radii of alkali metal ions, steric bulk of cAAC ligands and solvation/de‐solvation/recombination of the dimeric unit [(cAAC)P‐M(THF) x ]2 . Abstract : Cyclic alkyl(amino) carbene (cAAC)‐stabilized oligomeric alkali metal‐phosphinidenides have been isolated and characterized in the solid state upon reduction of chlorophophinidenes.